Analysis of the information in mandatory reporting in victims of gender violence - Belen Reynaldos; Faustina Sánchez-Rodríguez; Isabel Legaz; Eduardo Osuna (SAGE Publishing, 2018)
The healthcare professional plays a key role in the detection and subsequent channeling of a situation of violence to a judicial level for appropriate investigation. The mandatory reporting of gender violence has become a controversial issue among health care practitioners and victims. The objective of this study was to analyze the quality of the way in which injury reports on victims of gender violence is completed, through an analysis of the information they include, the readability and the degree to which the document can be understood. A retrospective study in a sample of 197 injury reports were performed from health services (primary care, hospital services and emergency services). We analyzed 22 variables related to the content, readability of the document, the victim's identification data as well as identification of the doctor responsible for assistance, the moment of assistance and the characteristics of the injury. The most frequent deficiencies in the data are identification of the doctor responsible for medical attention, the date on which the aggression occurred, a description of the injuries and the judgment of compatibility between the cause of injury (according to the victim) and the actual injury they have. The injury reports do not conform to the legal requirements needed in a document of such extraordinary importance. Greater awareness in health professionals concerning the importance of the injury report as a medicolegal document is needed so that the correct information can be provided to the relevant judicial authority.